The main theoretical and practical aspects of the functioning of the defense resource management system at the level of the Armed Forces of Ukraine - Semenenkо Oleh; Onofriychuk, Petro; Motrunych , Ivan; Ostapets , Oleh; Getman , Alevtina; Romanchenko , Olha (Social Development and Security, 2021)
Given the constant dynamics of the state of development of the national economy of the state, the influence of external and internal factors on the development of the Armed Forces of Ukraine, meeting the needs of their development in resources should be based on the principles of effective use and management of defense resources, both at the stage of formation of defense planning documents and during their direct execution. The adaptation of the military planning system in modern conditions of state development, as well as the development and reform of the Armed Forces of Ukraine, should be based on indicators of the required level of the country’s defense capability, taking into account the economic capabilities of the state to meet the needs for defensive resources. In the article, the authors clarified the concept of defensive resources, defined the concept of managing defense resources, and also defined the subjects and objects of managing defense resources at the level of the state and the Armed Forces of Ukraine; the external and internal context of the management of defense resources on a national scale was formed, as well as the structure of the main processes and interaction between the elements of the defense resource management system in the Armed Forces of Ukraine; clarified the vertical of units involved in the processes of managing defense resources in the Armed Forces of Ukraine; the main tasks of the objects of management of defense resources in the Ministry of Defense of Ukraine and the Armed Forces of Ukraine have been determined, and the basic principles of this process have been formed at the level of the state and the Armed Forces of Ukraine. Also, the authors in the article have identified the main indicators characterizing the efficiency of resource management in the formation and implementation of activities of programs and plans for the development of the capabilities of the Armed Forces of Ukraine. The main direction of further research on the topic of the article is the development of theoretical or methodological foundations for effective management of defense resources both at the level of the Armed Forces of Ukraine and at the state level.